Using of Laser Therapy in the Treatment of Patients With Plantar Fasciitis - Jaddue, Dhia AK; Al-dulaimi, Ali. Sulaiman. M. Said (AL-Kindy College Medical Journal, 2008)
Background: planter fasciitis is a common conditionseen in adults and sport men, it is characterized by dullpain in the heel, especially when getting up andstanding on the foot in the morning or after sitting for along time.Recently low level laser therapy is used as a method oftreatment.Objective: to evaluate the benefit of laser therapy intreatment of planter fasciitis.Methods: Out of twenty five patients with planterfasciitis exposed to laser therapy. Laser used is (diodetype) given in two cessions per week for four weeks,time for each cession is about (12 minutes).Results: complete recovery seen in (32%) of patients,moderate improvement in (16%), mild improvement in(24%), no response in (28%), deterioration (0%).Conclusion: laser therapy is safe for treatment ofplanter fasciitis, free of side effects, very effective asan alternative to surgery and local steroid injection,with no deterioration in the condition during or afterlaser therapy